2012
DOI: 10.1111/j.1365-2133.2012.11202.x
|View full text |Cite
|
Sign up to set email alerts
|

Actinic keratosis in theen-faceand slice imaging mode of high-definition optical coherence tomography and comparison with histology

Abstract: HD-OCT with both the en-face and slice imaging modes offers additional information in the diagnosis of AK compared with conventional OCT and might enhance the possibility of the noninvasive diagnosis of AK prior to treatment procedures and possibly in the monitoring of noninvasive treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 24 publications
0
62
1
1
Order By: Relevance
“…Imaging techniques such as OCT and RCM have been applied for various indications, including non-melanoma and melanocytic skin cancer [12,13,14]. Also, inflammatory reactions such as contact or allergic eczema and infestations with parasites have been studied using these techniques [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques such as OCT and RCM have been applied for various indications, including non-melanoma and melanocytic skin cancer [12,13,14]. Also, inflammatory reactions such as contact or allergic eczema and infestations with parasites have been studied using these techniques [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, field cancerization is defined as an area of subclinical changes in the periphery of visible AKs that displays the same genetic changes found in the lesion itself . New imaging techniques, such as reflectance confocal microscopy (RCM) and high‐definition optical coherence tomography (HD‐OCT), which allow visualization of the photodamage surrounding AKs, confirm that the disease often affects the entire sun‐exposed field (Fig. ) …”
Section: Field Cancerization Of the Skinmentioning
confidence: 99%
“…Various studies have investigated characteristics of sun damage and skin cancer in OCT, and their correlation with histological entities. In particular, it has been demonstrated that NMSC as actinic keratosis (AK), squamous cell carcinoma (SCC) and BCC have shown distinct features in OCT …”
Section: Introductionmentioning
confidence: 99%